THE ROLE OF AFFECTIVE COMMITMENT IN MEDIATING TRANSFORMATIONAL LEADERSHIP, PO-FIT AND PJ-FIT ON EMPLOYEE PERFORMANCE - Bagus Irfaan Madani; Dewi Andriani; Rifdah Abadiyah (LPPM STIE Muhammadiah Bandung, 2026)
This study aims to analyze the role of affective commitment in mediating the influence of transformational leadership, individual-organization fit, and job fit on employee performance in a steel manufacturing company. The research method uses a quantitative approach with a total sampling survey technique on employees from various divisions, through a Likert-scale questionnaire instrument (1–5). Data analysis was conducted using Structural Equation Modeling (SEM) using SMARTPLS 4 software to test direct and indirect relationships between variables. The results show that affective commitment, transformational leadership, individual-organization fit, and job fit have a direct positive effect on performance. In addition, individual-organization fit, job fit, and performance have a positive effect on affective commitment, while transformational leadership has no effect on affective commitment. These findings confirm that affective commitment is an important determinant that strengthens the influence of job fit on employee performance. This study provides theoretical contributions to the development of human resource management literature as well as practical implications for management in formulating leadership strategies and organizational policies oriented towards increasing employee affective commitment.